2020
DOI: 10.1111/jcmm.15124
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐9 promotes angiogenesis of endothelial progenitor cell to facilitate thrombi recanalization via targeting TRPM7 through PI3K/Akt/autophagy pathway

Abstract: Endothelial progenitor cells (EPCs) have emerged as a promising therapeutic choice for thrombi recanalization. However, this role of EPCs is confined by some detrimental factors. The aim of this study was to explore the role of the miR-9-5p in regulation of the proliferation, migration and angiogenesis of EPCs and the subsequent therapeutic role in thrombosis event. Wound healing, transwell assay, tube formation assay and in vivo angiogenesis assay were carried out to measure cell migration, invasion and angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…However, the limited capacities of homing and angiogenesis of EPCs impair their therapeutic effects. Intriguingly, our previous study demonstrated that miR-9 prevents apoptosis but promotes proliferation, migration, and angiogenesis of EPCs by targeting TRPM7, which enhances recanalization following venous thrombosis 24 . Although we identified the PI3K/Akt/autophagy pathway to be involved in the process, the effects of miR-9 on mRNA expression profiles of EPCs remain unclear.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the limited capacities of homing and angiogenesis of EPCs impair their therapeutic effects. Intriguingly, our previous study demonstrated that miR-9 prevents apoptosis but promotes proliferation, migration, and angiogenesis of EPCs by targeting TRPM7, which enhances recanalization following venous thrombosis 24 . Although we identified the PI3K/Akt/autophagy pathway to be involved in the process, the effects of miR-9 on mRNA expression profiles of EPCs remain unclear.…”
Section: Discussionmentioning
confidence: 89%
“…Autophagy has attracted attention as a potential therapeutic target for vascular disease, and the process plays an important role in vascular biology and homeostasis and is implicated in many physiological and pathological processes involving cell angiogenesis and migration 33 . Our previous studies have shown miR-9 to promote EPC migration, proliferation, and angiogenesis by regulating autophagy and MMP2 protein expression, thereby promoting thrombolysis and vascularization in DVT 24 . However, tissue inhibitor of matrix metalloproteinases (TIMPs), specific inhibitor of MMPs, had no significant differences in our RNAseq results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The role of miR-9 in angiogenesis is a promising therapy for many diseases. MiR-9 could promote migration, invasion, and angiogenesis of endothelial progenitor cells via downregulating transient receptor potential melastatin 7 (TRPM7) and activating PI3K/Akt/autophagy pathway, which might facilitate thrombi recanalization in deep vein thrombosis ( Zhou et al, 2020 ). Translocation of miR-9 from bone marrow-derived mesenchymal stem cells into vascular ECs could induce angiogenesis via activating PI3K/AKT pathway to repair the severe acute pancreatitis ( Qian et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that miR-9 promotes angiogenesis via activating the autophagy pathway ( Zeng et al, 2019 ). MiR-9 also promotes the angiogenesis of endothelial progenitor cells via activating the autophagy pathway ( Zhou et al, 2020 ). However, the molecular mechanism involved in miR-9-induced angiogenesis in ECs has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%